2011
DOI: 10.1063/1.3594239
|View full text |Cite
|
Sign up to set email alerts
|

Localization potentials in AlGaN epitaxial films studied by scanning near-field optical spectroscopy

Abstract: Scanning near-field photoluminescence spectroscopy has been applied to evaluate bandgap fluctuations in epitaxial AlGaN films with the AlN molar fraction varying from 0.30 to 0.50. A dual localization pattern has been observed. The potential of the small-scale (<100 nm) localization, evaluated from the width of the photoluminescence spectra, is between 0 and 51 meV and increases with increased Al content. These potential variations have been assigned to small-scale compositional fluctuations occurring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 27 publications
2
33
0
1
Order By: Relevance
“…Pinos et al reported that the potential variations were clearly observed in samples with lower relative Al content and were attributed to Ga-rich regions close to grain boundaries or atomic layer steps. 13 In our observations, all samples except the AlGaN epitaxial layer with relative Al content of 0.73 showed the same trend in terms of potential variation, where lower energy emission was observed at hillock edges, especially in samples with low relative Al content. In contrast, the AlGaN epitaxial layer with relative Al content of 0.73, which contained fewer hillocks, showed a rather small potential fluctuation likely originating from grains, but no characteristic emission at grain boundaries.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Pinos et al reported that the potential variations were clearly observed in samples with lower relative Al content and were attributed to Ga-rich regions close to grain boundaries or atomic layer steps. 13 In our observations, all samples except the AlGaN epitaxial layer with relative Al content of 0.73 showed the same trend in terms of potential variation, where lower energy emission was observed at hillock edges, especially in samples with low relative Al content. In contrast, the AlGaN epitaxial layer with relative Al content of 0.73, which contained fewer hillocks, showed a rather small potential fluctuation likely originating from grains, but no characteristic emission at grain boundaries.…”
Section: Resultssupporting
confidence: 63%
“…12,13 However, the excitation wavelength available in SNOM-PL and the relative Al content range to which it is applicable are limited to around 258 nm and about 0.50, respectively, due to damage to the optical fiber used as a SNOM probe. From this point of view, CL in combination with scanning electron microscopy (SEM) is another technique suitable for detecting optical inhomogeneities in AlGaN with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The model ensures good approximation for the PL band shape, quantitatively describes the temperature dependence of the band FWHM, and enables one to extract absolute values of the dispersion parameters σ and Γ. This model is applicable to describe the potential profile in InGaN [87], AlInGaN, [59,88] and AlGaN [89].The model of the double-scaled potential profile is also consistent with the recent results obtained by near-field optical spectroscopy of AlGaN epilayers with different Al content [90]. Potential fluctuations on a small spatial scale (<100 nm) were evaluated from the width of the photoluminescence spectra to be between 0 and 51 meV and to increase with increased Al content.…”
Section: Carrier Localizationsupporting
confidence: 72%
“…On the other hand, as sample A had less defined boundaries, as such, no correlation was observed. Pinos et al 28 highlighted a similar observation in AlGaN films and attributed the broader peaks at the boundaries to the more pronounced potential fluctuations around the grain boundaries relative to inside the grains. This phenomenon may be due to the higher concentration of different types of defects with non-uniform distribution near the boundaries, which causes inhomogeneous broadening.…”
mentioning
confidence: 63%